On the system of temps of Uzbek classical music - Rasulov Marufjon Mamirjon ogli (International Journal on Human-Computing Studies, 2021)
In this article we can see the temps that have become the basis of our Uzbek classical music. In the coverage of the subject of this temp, we can see that the issues of "Iyqa" are discussed in more detail, as well as scientifically. It is the opinions of our thinkers and scientists that have served as the basis for the detailed coverage of this article.